2008
DOI: 10.1111/j.1470-6431.2007.00656.x
|View full text |Cite
|
Sign up to set email alerts
|

Counting the cost of healthy eating: a Swedish comparison of Mediterranean‐style and ordinary diets

Abstract: The aim of this research was to examine the cost of a diet generally regarded as healthy, a Swedish version of the Mediterranean diet, and to compare it with the cost of an ordinary Swedish diet. A total of 30 individuals provided detailed dietary data collected in a randomized intervention study, examining the effect of dietary change to a Mediterranean‐style diet in patients with rheumatoid arthritis (Mediterranean group, n = 16, control group, n = 14). The data, covering 1‐month dietary intake, were examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 41 publications
7
24
1
Order By: Relevance
“…However, it is important to note conflicting findings in the literature. This includes Ryden et al finding that non‐energy adjusted costs were not different for an ordinary diet versus a Mediterranean diet and Ni Mhurchu & Ogra finding an insignificant cost difference between a regular basket of food versus healthy basket. Regardless of whether the expense of healthy foods and cheapness of unhealthy foods is accurate in reality, the perception of price strongly influences preference for unhealthy foods .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note conflicting findings in the literature. This includes Ryden et al finding that non‐energy adjusted costs were not different for an ordinary diet versus a Mediterranean diet and Ni Mhurchu & Ogra finding an insignificant cost difference between a regular basket of food versus healthy basket. Regardless of whether the expense of healthy foods and cheapness of unhealthy foods is accurate in reality, the perception of price strongly influences preference for unhealthy foods .…”
Section: Discussionmentioning
confidence: 99%
“…Mitchell et al [30] who examined the food costs in low fat diets of obese children found that there was no significant difference in food costs between the low fat diet and a control group. Moreover, Rydén et al [31] compared a Mediterranean diet to a standard Swedish diet and found no significant differences in non-energy adjusted costs between diets. Other researchers who have conducted cost benefit analyses of nutrition education programs have also found a significant decrease in spending after receiving nutrition education and advice [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Environmentally friendly and healthy food consumption is often considered more costly. Consumers vary in their willingness to pay for up-priced food products (Laroche et al, 2001;Krystallis et al, 2006;Rydén et al, 2008). We assume that the more the consequences of environmental pollution affect a consumer materially, the more (s)he is willing to accept premium prices.…”
Section: Materials and Immaterials Concernmentmentioning
confidence: 99%